Design and Development of Real-Time Monitoring & Controlling Infant Incubator with Tilt Stabilizer Using Raspberry Pi Remotely Controlled via PC and Smartphone to Reduce Tilt during Baby Transfer - Romadhon, Syaiful; Multi, Abdul (International Journal of Advanced Multidisciplinary, 2023)
This research aims to Design and Development of Real-Time Monitoring & Controlling Infant Incubator with Tilt Stabilizer Using Raspberry Pi Remotely Controlled via PC and Smartphone to Reduce Tilt during Baby Transfer. An experimental approach was used, involving data collection, controller determination, hardware design, circuit schematics, software design, and user interface development. Raspberry Pi was selected as the controller due to its sufficient GPIO pins for reading sensors and operating actuators. The tilt stabilizer was created using NEMA 17 stepper motor and a self-designed flexible screw nut to ensure precise tilt adjustment. During testing, the system demonstrated reliable performance, verified through analysis of test data and sensor readings on the HDMI-connected screen, and remote accessibility via PC and smartphone using the internet. The incubator's temperature consistently maintained 37°C using PID control. On an inclined surface of 20°, the tilt stabilizer effectively maintained a stable 10° inclination during baby transfers.